Repurposing Dihydroartemisinin-Piperaquine-Doxycycline as an Antimalarial Drug: A Study in Plasmodium berghei-Infected Mice - Udeme Owunari Georgewill; Elias Adikwu (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2021)
Artemisinin-based combination (ACT) therapy is the mainstay for malaria treatment. However, Plasmodium parasite with decreased susceptibility to ACT has emerged. Hence, it is imperative to discover new drugs or explore new drug combinations that can decrease Plasmodium parasite resistance. This study assessed the antiplasmodial activity of dihydroartemisinin-piperaquine- doxycycline (D-P-DX) on mice infected with Plasmodium berghei. Swiss albino mice (25-30g) of both sexes inoculated with 1x107 Plasmodium berghei intraperitoneally were used. The mice were randomly grouped and orally treated with DX (2.2 mg/kg), D-P (1.71/13.7 mg/kg) and D-P-DX daily in curative, suppressive and prophylactic studies. The negative and the positive controls were treated daily with normal saline (0.2mL) and chloroquine (CQ) (10mg/kg), respectively. After treatment, blood samples were assessed for percentage parasitemia, hematological and lipid parameters. Also, the mice were observed for mean survival time. D-P, DX, and D-P-DX produced significant decreases in percentage parasitemia at p<0.05, p<0.01 and p<0.001, respectively when compared to negative control. In the curative study, D-P, DX, and D-P-DX produced 64.9%, 71.1%, and 93.6% parasitemia inhibitions when compared to 70.0% inhibition produced by CQ. Plasmodium berghei -induced alterations in packed cell volume, white blood cells, red blood cells, hemoglobin, high-density lipoprotein cholesterol, total cholesterol, low-density lipoprotein cholesterol, and triglyceride levels were significantly restored by DX (p<0.05) and D-P (p<0.01) and D-P-DX (p<0.001) when compared to the negative control. D-P-DX showed significant antiplasmodial activity against Plasmodium berghei- infected mice. It may be clinically useful for the treatment of malaria.